An Analysis of Students’ Problems in Writing Recount Text - Shindy Ika Lestari Chandra; Syarifuddin Dollah; Geminastiti Sakkir; Harnita Rosalia (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aimed to find out strategies for students in writing recount text. This research design used a descriptive qualitative method. The subject of the research was Students at Grade 8th in SMP Laniang Makassar in the academic year of 2022/2023. The sample was 22 students in two classes and used purposive sampling to gain the data. The data was collected using a student’s writing and Interview. Based on the researcher’s result, the researcher found that there were various strategies to overcome problems encountered by the students in writing recount text, namely making lessons visually compelling, identifying important ideas, changing vocabulary learning, changing evaluation, and linking previous knowledge. In conclusion, the survey regarding the writing recount text for SMP Laniang Makassar students clearly illustrates the challenges faced and the strategies implemented.